Simulation of natural convention heat transfer in an enclosure using lattice boltzmann method - Che Sidik, Nor Azwadi; Rosdzimin, A. R. M. (Faculty of Mechanical Engineering, 2008)

(untitled)
In this paper, the thermal lattice Boltzmann method (LBM), a numerical tool based on particle distribution function is used to simulate steady state thermal fluid flow problems and compared with the established CFD tools; FLUENT. At low Rayleigh number simulation, D2Q9 lattice model was coupled with the simplest D2Q4 lattice model to represent density and internal energy density distribution function respectively. While at high Rayleigh number simulation, D2Q9 lattice model was used for both density and internal energy distribution functions. Simulation of natural convection of air in a rectangular enclosure with localized heating from below and symmetrical cooling from the sides was carried out. The paper demonstrates that the lattice Boltzmann model is a promising simulation tool for the simulation of natural convection heat transfer phenomena within a wide range of Rayleigh number values.